CULTURALLY-ROOTED SCHOOL LEADERSHIP: THE ROLE OF GUSJIGANG VALUES IN ENHANCING CHARACTER EDUCATION AT THE PRIMARY LEVEL - Jamaluddin Kamal; Ahsanul In’am; Khozin Khozin (Universitas Islam Negeri Mataram, 2025)
In culturally diverse educational contexts, school leadership often fails to reflect the values and wisdom inherent in local traditions. In Indonesia, character education often relies on normative approaches, overlooking the potential of indigenous philosophies to inform ethical and behavioral development. This study examines how Gusjigang—a cultural value system rooted in Islamic moralism, literacy, and entrepreneurship—is integrated into primary school leadership and character education in Kudus Regency, Central Java. Using a quantitative survey design, data were collected from 15 principals and 85 teachers across randomly selected public elementary schools through a 30-item Likert-scale questionnaire. The results show that the dimension of religious commitment (Gus) is highly embedded in both leadership practices (M = 3.72) and character education (M = 3.65), followed by literacy cultivation (Ji) and entrepreneurial modeling (Gang), which were implemented to a moderate extent. These findings suggest that while the moral and intellectual components of Gusjigang are well-integrated, its entrepreneurial aspects remain underdeveloped within school culture. The novelty of this study lies in its culturally responsive leadership framework, grounded in a local philosophical tradition, which contributes to the discourse on contextualized character education. Practically, the study suggests that educational leaders and policymakers should incorporate local wisdom into leadership development and curriculum design to enhance character education that is not only globally relevant but also locally resonant. This research affirms the transformative potential of indigenous values, such as Gusjigang, in cultivating holistic educational environments and ethical school communities.